The Concept of Parental Responsibility in Malaysia: An Analysis of Legal Literature (Kanun: Jurnal Undang-undang Malaysia, 2023)
This article is a study on the concept of parental responsibility in Malaysia. The intended responsibility is not only focused on child rearing and child support, but also covers every aspect of upholding the best interests of children. The issue of negligence, abuse, manipulation, the involvement of children in criminal behavior, and endless social problems have been discussed widely in previous studies. However, parental responsibility, especially its legal point of view, still requires a critical study. The writing of this article analyses parental responsibility from the perspective of early English legislation, its position in Islamic law, and the concept of parental responsibility in the legislation of Malaysia. The focus is specifically on parental responsibility towards children after divorce. Documentary analysis was performed on data from selected materials, including journal articles, books, and statutes. All data were obtained through literature review. The findings of this study show that the concept of parental responsibility in Malaysia has given rights to children and guarantees their interests, as well as guarantees the continued responsibility of parents.Keywords: Parental responsibility, post-divorce, children’s rights, best interests of children, civil, shariahFull text: PDF